Roman Epistles as a Genre Form in J. Brodskys Poetry (Global Journal of Human-Social Science, 2025)
In the literature of ancient Rome the emergence of the epistolary genre was due to the widespread spread of epistolary creativity during the period of the end of the era of civil wars and the formation of the empire. Epistola became the only means of communication and obtaining information in the giant Mediterranean power, whose territories were located on three continents. The letters, which initially had a purely private character, acquired information content, sociopolitical and philosophical content, the value of a public historical document and, finally, the format of a propaganda leaflet during Cicero's lifetime. Poets of the "Golden Age" actively used the wide possibilities of the epistolary genre. Horace creates an entire book of "Epistles", filling it with a wide variety of content, from philosophy and didactics to irony and ridicule. Ovid continues the line of love outpourings in the book "Heroids", creating in the spirit of rhetorical exercises the messages of mythological heroines to their lovers who left them.
Keywords: roman epistles; cicero; ovid; horace; dialogism; brodsky; culture of the “ready word”; mythological subjects